In Silico Evaluation of Some Commercially Available Flavonoids as Galactofuranoyltransferase- 2 Inhibitors in the Management of Tuberculosis - Madeswaran, Arumugam; Midhuna, Premavathi G. (Letters in Drug Design & Discovery, 2022)
Background: Galactofuranoyltransferase-2 (GlfT2) enzyme involved in the galactan polymerization of the arabinogalactan (AG) region of the mycolylarabinogalactan-peptidoglycan (mAGP) complex, an important component of the mycobacterial cell wall. Objective: With the existing challenge, the study focused on identifying certain commercially available flavonoids through molecular docking studies against the Galactofuranoyltransferase-2 enzyme. Methods: The initial pharmacokinetic screening was carried out using Lipinski’s rule of 5 with the help of Molinspiration software. In this perspective, Apigenin, Kaempferol, Rutin, Silibinin and Vitexicarpin were selected for the current study. Except for rutin all other selected flavonoids did not show any violations and were thereby selected for the docking studies using AutoDock 4.2. Results: The docking results showed that the selected flavonoids have excellent binding energy values between −8.98 to −6.58 kcal/mol against the GlfT2 enzyme. The theoretical inhibition constant was found to be in the range of 260.90 nM to 15.13 μM which coincides with the binding energies of the selected compounds. Conclusion: From the selected flavonoids, Silibinin showed excellent binding scores and has the potential to inhibit the GlfT2 enzyme. Silibinin could act as a novel GlfT2 inhibitor with promising therapeutic activity with low toxicity profile against tuberculosis.
Keywords: inhibition constant